Indonesia PEMANFAATAN STORYTELLING SEBAGAI ALAT PERSUASIF DALAM DAKWAH - Muhammad Irfan Affandi; Arya Alfarrel (STISIP Widyapuri Mandiri Sukabumi, 2026)
Da’wah as a process of religious communication requires effective message delivery strategies to engage the cognitive, affective, and psychomotor dimensions of the audience. This study aims to analyze the use of storytelling as a persuasive tool in da’wah by examining the role of narrative structure, emotional elements, and rhetorical approaches in enhancing the effectiveness of religious messages. The research employs a descriptive qualitative method with a literature review approach and content analysis techniques applied to various relevant academic publications. The findings indicate that storytelling functions as a strategic persuasive instrument through the principles of coherence (logical narrative flow) and fidelity (alignment with the audience’s lived experiences). In traditional contexts, the use of stories of prophets and past communities provides strong educational and emotional value. Meanwhile, in the digital era, the transformation of da’wah through platforms such as TikTok, YouTube, and WhatsApp demonstrates that authentic and relatable audio-visual narratives are more effective in increasing audience attention and message retention than conventional instructional methods. This study concludes that storytelling represents an adaptive communicative solution for preachers in addressing the challenges of the digital information flow, enabling Islamic messages to be internalized in an inclusive and engaging manner by modern society.